The relationship between self esteem and locus of control with infertility related stress of no related infertile men and women - T Alizadeh; MN Farahani; M Shahraray; Sh Alizadegan (JRI, 2005)
Introduction: As infertility is known as a physiological effect, it is also a psycho-social effect. Recently, there are a lot of developing research showing that psychological factors can be a cause of infertility, and also infertility can have psychological outcomes. From psychological factors, it should be to address of infertility- related stress, Internal- External locus of control and self esteem .The Objective of the Study was to investigate the relationship between infertility- related stress (sexual, social, relationship, rejection of child- free life style and need for parenthood) with self- esteem and locus of control in non- related infertile men and women in Tehran, Iran. Materials and Methods: sixty infertile men and women (Not related together), were selected randomly from Royan Infertility clinic in summer-winter, 2003, they were completed Newton`s Fert-ility Problem Inventory(1999), Rosenberg’s Self-Esteem Questionnaire(1990), and Levenson`s Inter-nality, Powerful-Others and Chance Locus of Control Scales (1975). Statistical Analysis was done with by using SPSS software. Results: The results showed a significant negative relationship (p<0.05) between self- esteem and components of (sexual, social, relationship, rejection of child- free life style and need for parenth-ood) infertility- related stress. Sexual issues had the highest correlation with self-esteem. Significant relationship (p<0.05) was found between external locus of control (believing in powerful others) and sexual, relationship, social, and rejection of child- free life style. The relationship between external locus of control (chance) and the relationship and need for parenthood components were also signi-ficant (p<0.05). Although the difference between infertility- related stress of men and women was significant, women in comparison with men had higher scores in all components. Sexual issues in women and relationship issues in men had the highest correlation with their self- esteem of all the components. Conclusion: According our result in infertility investigation, the psychological factors have Relative importance, and in the future researches, it is necessary to go behind psychological factors such as social factors.
Keywords: Infertility, Stress, Self- esteem, Locus of control, Sex differences